"I keep it to myself": A qualitative meta‐interpretive synthesis of experiences of postpartum depression among marginalised women. (4th September 2018) - Maxwell, December; Robinson, Sarah R.; Rogers, Kelli
Abstract: Postpartum depression (PPD) is a significant public health concern due to the physical, emotional, economic, and life course outcomes. Rates of PPD are significantly higher for marginalised populations and can impact low‐income, minority, and/or immigrant women differently when compared to white middle‐class women. Commonly studied negative effects of PPD include poor health outcomes, mother–child bonding challenges, and negative child educational outcomes. However, research surveying the postpartum experience and negative outcomes among marginalised women is sparse. This study implemented a qualitative meta‐interpretive synthesis (QIMS) methodology to synthesise themes across 12 qualitative research articles surveying postpartum experiences of marginalised women in North American countries. Articles included in the QIMS were extracted from online databases from a 10‐year window spanning January 2008–2018. The guiding research question was "What are the PPD experiences of women belonging to marginalized populations?" Constant comparative analysis was used with coding in atlas.ti and themes were synthesised with input of all three authors. Five main themes emerged. The themes are (a) intersections of PPD and poverty, (b) culture and PPD, (c) pressures of mothering, (d) strengths and coping, and (e) abuse affects my PPD experience. Subthemes such as "I keep it to myself" relating to cultural response to PPD and idealised mothering were also discovered. Implications for social workers, nurses, and future research are discussed.